2010
DOI: 10.1096/fj.10-169383
|View full text |Cite
|
Sign up to set email alerts
|

The AMPKyl subunit plays an essential role in erythrocyte membrane elasticity, and its genetic inactivation induces splenomegaly and anemia

Abstract: AMP-activated protein kinase (AMPK) is an αβγ heterotrimer conserved throughout evolution and important for energy sensing in all eukaryote cells. AMPK controls metabolism and various cellular events in response to both hormones and changes in cellular energy status. The γ subunit senses intracellular energy status through the competitive binding of AMP and ATP. We show here that targeted disruption of the mouse AMPKγ1 gene (Prkag1) causes regenerative hemolytic anemia by increasing the sequestration of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
8
27
0
Order By: Relevance
“…This can be explained by the importance of heterotrimeric complex in the stabilization of individual AMPK subunit. AMPK is stable as a heterotrimer complex, whereas each of its subunits is subject to an increased turnover rate and is depleted from the cell when not associated with others (41)(42)(43). Therefore, the observed higher expression of AMPK␤1 in AMPK␣ Ϫ/Ϫ MEFs indicates that the transduction of the Ad-DN resulted in an increase in the AMPK heterotrimer complex in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the importance of heterotrimeric complex in the stabilization of individual AMPK subunit. AMPK is stable as a heterotrimer complex, whereas each of its subunits is subject to an increased turnover rate and is depleted from the cell when not associated with others (41)(42)(43). Therefore, the observed higher expression of AMPK␤1 in AMPK␣ Ϫ/Ϫ MEFs indicates that the transduction of the Ad-DN resulted in an increase in the AMPK heterotrimer complex in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…75-886) in accordance with European guidelines. The generation of AMPKγ1 −/− mice has been previously described (10). Global AMPKγ2 −/− mice were generated by deleting the entire exon 7 of the gene encoding AMPKγ2 in R299Q knockin mice using Sox2cre-driven excision (48).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, AMPK can regulate mitochondrial cardiolipin content (40), and this lipid is known to regulate bacterial HAS (39). As cardiolipin is typically in the mitochondria, this issue could be not critical for eukaryotic HASs, although very recently, it was reported that the AMPK ␥1 subunit can control erythrocyte membrane elasticity (41). Therefore, AMPK could modify membrane lipid composition indirectly by modulating HAS activity or stability.…”
Section: Ha Does Not Influence Ampk-mediated Reduction Of Cellmentioning
confidence: 99%